2010
DOI: 10.1177/0961203310378413
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life predictor factors in patients with SLE and their modification after cognitive behavioural therapy

Abstract: QOL usually depends on multiple factors, some of which are stress and anxiety, which can be modified by a cognitive behavioural therapy, in order to obtain a significant improvement in the HRQOL, irrespective of the activity level of the disease. Frequent evaluations of the quality of life in patients with SLE and psychological treatment should also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 28 publications
0
43
0
16
Order By: Relevance
“…Many of the SLE symptoms interfered in several areas of the patient´s life [22] and consequently in their quality of life [7,8] and consequences can include giving up regular work [2,19,21] and daily activities, as the results above show. Nevertheless, resilience can be a contributing factor so that these patients can change their lifestyle but maintain their activities as far as possible because resilience is successful adaptation in spite of adversity or stress and implies efficacious performance of daily activities [12,13, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the SLE symptoms interfered in several areas of the patient´s life [22] and consequently in their quality of life [7,8] and consequences can include giving up regular work [2,19,21] and daily activities, as the results above show. Nevertheless, resilience can be a contributing factor so that these patients can change their lifestyle but maintain their activities as far as possible because resilience is successful adaptation in spite of adversity or stress and implies efficacious performance of daily activities [12,13, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic Lupus Erythematosus (SLE) is a chronic autoimmune, rheumatic inflammatory disease that can affect several organs and systems in the body, causing significant morbidity [1-3] with evident psychological impacts [3,4] such as anxiety and depression [5,6] and obvious harm to life satisfaction [3] and quality-of-life [7,8] that require the patient to adapt treatment and the situation of living with a chronic disease. It is more common in young persons, especially women [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, self-management programs may work to decrease stress among SLE patients (29). Cognitive behavioral therapy has also been shown to decrease perceived stress in the SLE population (30). In another randomized study of SLE patients (32), a stress reduction program consisting of biofeedback-assisted cognitive behavioral therapy reduced pain perception and improved psychological and physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that cognitive behavioural therapy with/without exercise is effective in reducing fatigue in chronic fatigue syndrome, multiple sclerosis, cancer-related fatigue and SLE because it improves self-efficacy, increasing their quality of life. (Edmonds et al, 2004;Navarrete-Navarrete et al, 2010;Neill et al, 2006;Wagner & Cella, 2004) …”
Section: Fatiguementioning
confidence: 99%
“…(Freire et el, 2011;McElhone et al, 2007;Sanchez et al, 2009;Thumboo & Strand, 2007) Cross-sectional studies and prospective studies have identified the age, the duration, the activity and damage disease, some specific manifestations of SLE as fatigue, pain or endstage renal failure, the corticosteroids or cytotoxic, the knowledge of lupus, the illness related behaviours, the educational status, the self-efficacy, the learned helplessness, the ability to work, the home environment and the social support as factors associated may influence health-related quality of life (HRQOL) in SLE patients. (McElhone K et al, 2006;Navarrete-Navarrete et al, 2010;Thumboo & Strand, 2007) …”
Section: Lupus Quality Of Lifementioning
confidence: 99%